2004
DOI: 10.3766/jaaa.15.7.5
|View full text |Cite
|
Sign up to set email alerts
|

Speech Intelligibility of Young School-Aged Children in the Presence of Real-Life Classroom Noise

Abstract: We examined the ability of 40 young children (aged five to eight) to understand speech (monosyllables, spondees, trochees, and trisyllables) when listening in a background of real-life classroom noise. All children had some difficulty understanding speech when the noise was at levels found in many classrooms (i.e., 65 dBA). However, at an intermediate (-6 dB SNR) level, kindergarten and grade 1 children had much more difficulty than did older children. All children performed well in quiet, with results being c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
77
0
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(84 citation statements)
references
References 13 publications
4
77
0
3
Order By: Relevance
“…One side effect of literacy could be that it helps readers to specify phonological representations in order to overcome difficulties in speech perception in noisy environments. Indeed, in a recent study, Jamieson, Kranjc, Yu, and Hodgetts (2004) demonstrated a qualitative jump from relatively poor speech intelligibility in noise in kindergarten and Grade 1 to relatively good speech intelligibility in Grades 2 and 3. Obviously, one of the major changes between Grades 1 and 2 is the acquisition of literacy.…”
Section: Discussionmentioning
confidence: 99%
“…One side effect of literacy could be that it helps readers to specify phonological representations in order to overcome difficulties in speech perception in noisy environments. Indeed, in a recent study, Jamieson, Kranjc, Yu, and Hodgetts (2004) demonstrated a qualitative jump from relatively poor speech intelligibility in noise in kindergarten and Grade 1 to relatively good speech intelligibility in Grades 2 and 3. Obviously, one of the major changes between Grades 1 and 2 is the acquisition of literacy.…”
Section: Discussionmentioning
confidence: 99%
“…An improved understanding of the development of SRM in children with normal hearing (NH) is important because they experience much difficulty when listening to speech in competing sounds (Elliott et al, 1979;Byrne, 1983;Jamieson et al, 2004). This knowledge is also important for examining the impact of the presence of hearing loss on the development of SRM in hearing-impaired children and for developing strategies to alleviate difficulties encountered by them in real life (Ching et al, 2010;Scollie et al, 2010a).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, self-reported mental well-being has been rated lower by children exposed to higher levels of community noise (7). In the pedagogic field, noise, defined as unwanted sound, has well-known negative effects on hearing ability in schools (8). Noise also affects concentration (9, 10), performance (11), reading, and memory (12)(13)(14).…”
mentioning
confidence: 99%